PENGARUH PEMBELAJARAN JARAK JAUH BERBASIS VIRTUAL LEARNING TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPS (Penelitian Quasi Eksperimen di Kelas VII SMPN Laboratorium UPI) - Silni Asfia, - (2020)
The background of the research is motivated by the fact that distance learning was fulfilled during the Covid-19 pandemic. Social studies education developed learning activity which required using appropriate technology with current circumstances. Thus, it needed an integration in distance learning based on virtual learning to develop student learning interest in learning Social studies.This study was intended to determine the influence of distance learning based on virtual learning in student learning interest in social studies of SMP Laboratorium UPI. The findings of the study were: 1) There is a difference between before distance learning based on virtual learning with after distance learning based on virtual learning in experiment class; 2) There is no difference between before distance learning based on virtual learning and after distance learning based on virtual learning in control class; 3) There is a significant difference of applying distance learning based on virtual learning in control class is 0.515 and experiment class is 0,006; 4) There is obstacle in distance learning based on virtual learning to student learning interest. The result of the study recommended that distance learning based on virtual learning can be developed and improved with using advanced technology to use in school learning activity.